WELL-BEING AND LIFE QUALITY AMONG OLD PEOPLE LIVING AND NOT LIVING IN INSTITUTIONS FOR THE ELDERLY - Molina Sena, Cristina; Meléndez Moral, Juan Carlos; Navarro Pardo, Esperanza (Anales de Psicología / Annals of Psychology, 2008)
Life quality improvement should constitute a priority in intervention with the elderly. In order to accomplish this objective a careful consideration of potential differences between elder people living in institutions and those living within a familiar context, with respect to wellbeing, is needed to better plan psychological interventions. Therefore a comparison of both groups of elder people was performed. Results shown a lower level of satisfaction of the group living in institutions compared to those living in a family context. Concretely, differences were found in social relationships and support and also perceived security levels. With respect to well-being, there were no differences between both groups in psychological well-being, but elder people living in institutions had lower level of subjective well-being than those living within a familiar context.